Socioprofessional relations in the hospital setting and repercussions on nursing staff’s mental health - Monteiro, Janine Kieling; Grisa, Gabrielle Hennig (Revista de Psicologia da IMED, 2014)
Studies point that conflicts in labor relations in the hospital context have influence in the illness of health care workers. A limited amount of studies about established relations by this group and mental health of workers were observed. A qualitative study was developed in order to characterize factors which produce pleasure and suffering in the workplace relations (co-workers, leadership and patients) and its repercussions in nurse's mental health. A total of 19 nurses and nursing technicians of a private hospital network were interviewed. The results were evaluated by means of content analysis, suggest that following patient's improvement, having professional recognition, freedom and helping at work are sources of pleasure. However, the lack of professional recognition, complaints and risk of patient's death, individualism, demands and lack of commitment are factors which produce suffering. Irritation, stress, headache, loss suffering, satisfaction and personal accomplishments  were mentioned as factors deriving from these relations. We suggest the necessity of more studies about the thematic, as well as more listening spaces for these professionals.